2007
DOI: 10.1007/s00380-006-0968-3
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone induces circadian gene expression of clock genes in H9c2 cardiomyoblasts

Abstract: We examined mRNA expression of the clock genes (Per1, Per2, and Bmal1) and PAI-1 (plasminogen activator inhibitor-1) after aldosterone treatment every 4 h up to 48 h in H9c2 cardiomyoblasts by reverse transcription-polymerase chain reaction. To block the MR (mineralocorticoid receptor), the MR antagonist, spironolactone, was added to the medium 1 h before aldosterone treatment. Aldosterone induced an initial increase and rhythmic expression of Per1, while spironolactone attenuated the acute increase in Per1 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Cortisol has been proposed as a synchronizing signal yet adrenalectomized animals still exhibit strong circadian fluctuations in physiological function (Moore-Ede, 1986). Our identification of Per1 as an aldosterone target gene has been validated by the findings of several other groups that aldosterone induces Per1 expression in the kidney and cardiomyoblasts (Tanaka et al , 2007; Le Billan et al , 2015). Per1 appears to be unique among the clock genes in being induced by aldosterone and cortisol.…”
supporting
confidence: 61%
“…Cortisol has been proposed as a synchronizing signal yet adrenalectomized animals still exhibit strong circadian fluctuations in physiological function (Moore-Ede, 1986). Our identification of Per1 as an aldosterone target gene has been validated by the findings of several other groups that aldosterone induces Per1 expression in the kidney and cardiomyoblasts (Tanaka et al , 2007; Le Billan et al , 2015). Per1 appears to be unique among the clock genes in being induced by aldosterone and cortisol.…”
supporting
confidence: 61%
“…Microarray analysis in a human adrenocortical cell line after angiotensin II treatment demonstrated that Per1 was upregulated 3-fold compared with control (24). Per1 and Per2 were induced by aldosterone in cardiomyoblasts, an effect that was blocked by spironolactone (32). Another connection between hormone signaling and Per1 was demonstrated by Balsalobre et al They found that glucocorticoids reset circadian timing in peripheral tissues, including the kidney, by inducing the expression of Per1 (33).…”
Section: Discussionmentioning
confidence: 92%
“…52 The deposition of fibrotic tissue, by decreasing gap junctions coupling and creating muscle bundle discontinuities, alters the spatial location and propagation of depolarization waves, thereby reducing conduction velocity and promoting re-entry circuits. 52,53 Because of the relatively low membrane potential of fibroblasts (-30 mV), fibroblast-cardiomyocyte coupling promotes delayed after-depolarization of the cardiomyocytes and ectopic firing. 52 It also increases transient Ca 2+ amplitude, leading to increased intracellular Ca 2+ concentrations and spontaneous sarcoplasmic reticulum Ca 2+ release, finally favoring AF maintenance 52 (Figure S1).…”
Section: Aldosterone Favors Inducible Atrial Arrhythmiasmentioning
confidence: 99%